Haemolacria as an early indicator of central precocious puberty in a physically active child: Implications for sports vision screening - Varshney, Ankit Sanjay; Mehta, Sanjay; Mukhopadhyay, Debapriya (Tanjungpura Journal of Coaching Research, 2026)
Background Haemolacria is a rare ocular condition characterized by blood in tears, with causes ranging from local ocular abnormalities to systemic and hormonal factors. In pediatric populations engaged in physical activity and sports, unusual ocular symptoms may be overlooked or misinterpreted as minor or trauma-related conditions. Objectives This study aims to describe a case of haemolacria preceding central precocious puberty (CPP) and to highlight its relevance in sports vision and pediatric screening. Methods This study used a descriptive case report design. A 9-year-old physically active girl presented with intermittent unilateral haemolacria. Comprehensive ophthalmic, otorhinolaryngological, and haematological evaluations were normal. After five months, the patient developed secondary sexual characteristics. Endocrine evaluation confirmed CPP based on a pubertal luteinizing hormone response, advanced bone age, and normal brain imaging. The patient was treated with GnRH agonist therapy. Results Results showed complete resolution of haemolacria following hormonal treatment, with no recurrence during 12 months of follow-up.  Visual acuity and intraocular pressures were within normal limits. Slit-lamp examination revealed a quiet conjunctiva with no identifiable bleeding focus. Lid eversion showed no granuloma or vascular lesion. The lacrimal sac was non-tender with no evidence of reflux. These findings suggest a possible hormonal mechanism underlying the ocular manifestation. Conclusion In conclusion, haemolacria may serve as an early indicator of systemic hormonal changes. In the context of sports and physical activity, early recognition of such symptoms is important for ensuring safe participation and optimal development in pediatric populations.